Extracellular ATP activates MAP kinase cascades through a P2Y purinergic receptor in the human intestinal Caco-2 cell line - Buzzi, Natalia Sol (2009)
Background: ATP exerts diverse effects on various cell types via speci fi c purinergic P2Y receptors. Intracellular signaling cascades are the main routes of communication between P2Y receptors and regulatory targets in the cell. Methods and results: We examined the role of ATP in the modulation of ERK1/2, JNK1/2, and p38 MAP kinases (MAPKs) in human colon cancer Caco-2 cells. Immunoblot analysis showed that ATP induces the phosphorylation of MAPKs in a time- and dose-dependent manner, peaking at 5 min at 10 μM ATP. Moreover, ATP γ S, UTP, and UDP but not ADP or ADP β S increased phosphorylation of MAPKs, indicating the involvement of, at least, P2Y 2 /P2Y 4 and P2Y 6 receptor subtypes. RT – PCR studies and PCR product sequencing supported the expression of P2Y 2 and P2Y 4 receptors in this cell line. Spectro fl uorimetric measurements showed that cell stimulation with ATP induced transient elevations in intracellular calcium concentration. In addition, ATP-induced phosphorylation ofMAPKs in Caco-2 cells was dependent onSrcfamily tyrosinekinases, calcium in fl ux, and intracellular Ca 2+ release and was partially dependent on the cAMP/PKA and PKC pathways and the EGFR. General signi fi cance: These fi ndings provide new molecular basis for further understanding the mechanisms involved in ATP functions, as a signal transducer and activator of MAP kinase cascades, in colon adenocarcinoma Caco-2 cells.